B33 Decreased heart mass and dysregulated cardiac mTORC1 activity are associated with huntington's disease. (13th September 2016) - Child, Daniel; Lee, John; Davidson, Beverly L
Abstract : Background: Huntington's disease (HD) profoundly affects the central nervous system, but the causative protein, mutant huntingtin (HTT), is expressed throughout the body. HD-related pathology may therefore occur in other organ systems. Importantly, cardiovascular disease is the second leading cause of death among HD patients, and cardiac abnormalities have been reported in HD patients and models, but the mechanism of pathogenesis is unknown. Activity of mTORC1, a regulator of growth and metabolism, is dysregulated in the brain in HD, and similar dysregulation in the heart may explain heart phenotypes observed in HD. Aims: To ascertain the natural history of cardiac pathology in HD, and to characterise mTORC1 dysregulation in the HD heart. Methods: Hearts from two different HD murine models, the transgenic N171-82Q and the knock-in zQ175, were studied by standard histological and biochemical techniques and by echocardiography. Results: Disease in HD mouse models is associated with smaller gross heart mass. When tracked over time, hearts in disease animals initially gain mass appropriately, but fail to maintain the same rate of mass increase as WT littermates after symptom onset. Interestingly, evidence at the functional, tissue, and cellular levels suggests lack of heart failure. Analysis of the mTORC1 pathway revealed decreased mTORC1 activity in the hearts of HD animals that is not the result of decreased axis activation or increased energy stress. Finally, systemic treatment with an AAV9-transduced anti-HTT miRNA gene restored many molecular abnormalities observed in HD animal hearts. Conclusions: These studies suggest that mutant HTT is not sufficient to cause heart failure. Additionally, mTORC1 activity may be impaired by cardiac expression of mutant HTT through as yet unknown cellular mechanisms, and may contribute to decreased heart mass. These findings have implications for the ability of the heart to respond to stress, and may help explain the mortality from heart disease in HD patients.